How does climate change mitigation drive the achievement of the SDGs? - Yomayuza, Karoll Valentina (2024)
Countering the negative effects of climate change has gone from being an environmental concern to becoming a cross-cutting priority in all development agendas. It is not just a matter of reducing greenhouse gas emissions; it also represents an opportunity to drive sustainable development and thus improve people's quality of life.